Empowering Students’ Problem-Solving Skills through the RADEC Model on Flood Topic - Silfa Dwi Nurani; Ani Nur Aeni; Atep Sujana; Ahmad Zaldi (Jurnal Pendidikan MIPA, 2026)
Education in the 21st century requires students to have various important skills, one of which is problem-solving skills. However, many students still experience difficulties solving problems and applying scientific knowledge to contextual situations. To support the development of problem-solving skills, teachers need to implement learning models that actively involve students. Effective learning provides opportunities for students to explore ideas, discuss, and build knowledge independently. Thus, this research aims to enhance students' problem-solving skills by applying the RADEC (Read, Answer, Discuss, Explain, and Create) model to the topic of flooding in science learning in elementary schools. This research uses a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research involved 30 fifth-grade students in the experimental class and 24 in the control class. Data collection was carried out using descriptive tests to measure students' problem-solving skills and observation sheets to document the implementation of the learning model. Data analysis included a normality test, a homogeneity test, independent sample t-test, and N-Gain analysis. The research results indicate that the application of the RADEC learning model falls into the very good category based on the observations. The average score of students' problem-solving skills in the experimental class increased from 59.63 in the pretest to 72.47 in the posttest, while in the control class it increased from 54.38 to 64.12. The results of the hypothesis test indicated a significant difference between the two groups (p < 0.05). In addition, the N-Gain analysis results show an increase in the medium category in the experimental class and a decrease in the low category in the control class. These findings indicate that the RADEC learning model effectively empowers students' problem-solving skills through contextual learning on flood-related topics. Keywords: RADEC learning model, problem-solving skills, flood natural disaster, science learning, elementary school.